Sistema de registro de preços nas aquisições de bens : estudo de caso na Polícia Militar do Espírito Santo no período de 2007 a 2012 - Zamprogno, Hanne Cardoso de Rezende (2013)
The Public Administration to carry out the acquisition of goods, it must do it through a public tender procedure. The public tender law provides that, preferably, purchases should be made through registration pricing. The registration system price is a public tender process, the modality or trading competition, through which will be chosen and recorded the advantage offer for Administration. The Military Police of Espirito Santo (PMES), an agency of the state executive, from the year 2007 gradually began to use this system for the procurement of goods. Given this change of PMES in public procurement, asked as the use of the log pricing system, administrative practice for the acquisition of goods, may be more advantageous for PMES. This study aimed to analyze the use of this system in public procurement carried out by PMES in the period 2007-2012, compared to purchases by conventional public procurement in order to maximize their advantages and minimize their disadvantages. For this, we used a qualitative research approach with descriptive nature, to expose the characteristics of this phenomenon, and as a research technique case study. Sought to identify the advantages and disadvantages of the use of the log pricing system in the acquisition of assets of PMES, through the analysis of 66 cases per public tender and the purchase price registry and interviewed three servers work in prosecution. It was found that the use of the log pricing system for acquisition of goods is required, however the administrative practices has not enabled the institution to get the advantages that the registration system can offer prices. In order to reverse this scenario, proposals that will enable optimizing and improving administrative practices for the use of price registration system to bring advantage PMES were presented.